Frances Bissell: The Floral Baker: Cakes, Pastries and Breads - Galizia, Helen Caruana (Petits Propos Culinaires, 2015)
Frances Bissell: The Floral Baker: Cakes, Pastries and Breads: Serif Books, 2014: 176 pp., paperback, £10.